Self-regulation of pollution: The role of market structure and consumer information - Devon A. Garvie (Fondazione Eni Enrico Mattei (FEEM), 1997)
A Cournot-Nash oligopoly model is used to study self-regulation of industrial pollution emissions. Consumers have environmental preferences such that demand is decreasing in their knowledge of industrial emissions. Symmetric firms choose output and emission control input levels. Under company-level voluntary codes, firms noncooperatively choose output and emission control input levels simultaneously. Under a regime of industry-level voluntary codes, an industry association chooses the industry profit-maximising level of emission control input to be adopted by all members of the industry and then firms noncooperatively choose output levels, taking the industry code as fixed. The oligopoly solutions are compared to the Pareto efficient solutions. A firm's incentive to voluntarily abate pollution is a price increase which can be realised by installing abatement technology (the installation of abatement technology by any individual firm results in an outward shift in the demand curve). The incentive to voluntarily comply is positively related to a firm's market power: if firms are price-takers, then the positive price effect, hence the incentive to voluntarily abate, is absent. Abatement effort is also a public good which leads to a dampening in adoption incentives and a free rider problem. In general, the efficiency losses from voluntary regimes are increasing in the level of competitiveness in the industry and decreasing in the toxicity of the pollutant. Hence, voluntary regimes work best in controlling cumulative pollutants in highly concentrated industries and are unsuitable for controlling noncumulative pollutants in highly competitive industries. Industry-level codes result in higher output and emission control input levels than company-level codes since industry co-ordination can resolve the free rider problem.
Keywords: 330; Oligopol; Internalisierung externer Effekte; Umweltmanagement; Umweltbelastung; Präferenztheorie; Nash-Gleichgewicht; Konsumtheorie; Theorie